2005
DOI: 10.1128/jvi.79.7.4229-4237.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 18 E6 Protein Binds the Cellular PDZ Protein TIP-2/GIPC, Which Is Involved in Transforming Growth Factor β Signaling and Triggers Its Degradation by the Proteasome

Abstract: In addition to the function they exert in virus replication, viral proteins often strongly interfere with cell physiology by interacting with cellular factors involved in important regulatory networks. Hence, the viral proteins, especially those expressed by DNA or RNA transforming viruses, represent interesting models to better understand cellular regulatory pathways. Along this line, the discovery of the ability of proteins expressed by different viruses to bind various cellular proteins with PSD-95-Discs-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 51 publications
0
54
0
Order By: Relevance
“…Because we were able to detect a significant level of Syx2 expression only in malignant cells, we hypothesize that the less tightly regulated Syx2, which gives rise to a sustained basal level of RhoA activity, up-regulates tumorigenic transcription factors. Association between tumorigenicity and Syx2 expression is suggested also by a previous study, which reported that synectin degradation mediated via its interaction with the viral oncoprotein E6, as well as RNAi silencing of synectin, increased cell proliferation (Favre-Bonvin et al, 2005). Together with the results presented here, this initial data set suggests a novel mechanism of malignant transformation that does not involve truncation of proto-oncogenic Rho GEF (Ron et al, 1989), but rather the expression of an unmodified and loosely targeted Rho GEF splice variant.…”
Section: Discussionmentioning
confidence: 78%
“…Because we were able to detect a significant level of Syx2 expression only in malignant cells, we hypothesize that the less tightly regulated Syx2, which gives rise to a sustained basal level of RhoA activity, up-regulates tumorigenic transcription factors. Association between tumorigenicity and Syx2 expression is suggested also by a previous study, which reported that synectin degradation mediated via its interaction with the viral oncoprotein E6, as well as RNAi silencing of synectin, increased cell proliferation (Favre-Bonvin et al, 2005). Together with the results presented here, this initial data set suggests a novel mechanism of malignant transformation that does not involve truncation of proto-oncogenic Rho GEF (Ron et al, 1989), but rather the expression of an unmodified and loosely targeted Rho GEF splice variant.…”
Section: Discussionmentioning
confidence: 78%
“…Endogenous activation of antiviral genes in a cell containing a ''selectable'' HPV16 integrant induces a decrease in episome content, with proportionate reduction in episomal expression of E2, E6, and E7. Reduced E6 and E7 will lead to reduced inhibition of type I IFN-inducible genes (19)(20)(21)(22) and the TGF-␤ pathway (23)(24)(25). These events would account for decreased expression of cell cycle genes (17,26), and would also lead to rapid further reduction in episome levels in a positive feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by induction of expression of catalytic subunit of Human Telomerase Reverse Transcriptase (hTERT) by forming a complex with E6-associated protein (E6AP) and binding to hTERT promoter [7,9,10,30,45]. Enhanced expression of hTERT prevents telomere shortening at the end of each cell division, since shortening of telomere length in each cell division corresponds to aging process; therefore constitutive expression of hTERT causes the cell to divide indefinitely causing immortalization.…”
Section: Introductionmentioning
confidence: 99%